A comparison of national immunization rates to immunization rates of Latino diabetic patients receiving clinical pharmacist interventions in a federally qualified community health centre (FQHC). Issue 3 (6th August 2014) - Padilla, Margie E; Jiang, Shan; Barner, Jamie C; Rivera, Jose O
Abstract: Objectives: To compare national immunization rates to immunization rates of Latino patients receiving clinical pharmacist interventions in a federally qualified community health centre (FQHC) in 2010. Methods: This is a retrospective electronic medical record (EMR) review conducted in an FQHC in El Paso, Texas. Adults (≥18) with diabetes who were seen by a clinical pharmacist between 1 January 2010 and 31 December 2010 were queried on the basis of 2010 vaccination criteria for the following vaccines: hepatitis A (HepA), hepatitis B, influenza, pneumococcal, tetanus-diphtheria-acellular pertussis (Tdap) and zoster. Each patient's EMR was reviewed to calculate immunization rates. Study immunization rates (SIRs), overall national immunization rates (OIRs) and national Hispanic immunization rates (HIRs) were compared using z -tests for proportions. The SIRs for each vaccine were calculated using the following formula: number of patients vaccinated/number of eligible patients. OIRs and HIRs were obtained from the 2010 National Health Interview Survey. Key findings: Patients ( n = 330) were 56.1 ± 12.7 years, primarily women (73.9%) and Latinos (96.7%). SIRs of HepA (33.3%), pneumococcal-ages 19–64 (46.2%) and Tdap (42.7%) were significantly ( P < 0.0001) higher when compared with both HIRs (10.3%, 14.8%, 4.8% respectively) and OIRs (10.7%, 18.5%, 8.2% respectively). Regarding zoster, the SIR (10.0%) was significantly ( P < 0.05) higher than the HIR (4.4%) but not significantly different from the OIR (14.4%). Conclusion: Clinical pharmacists can play a significant role in increasing adult vaccination rates. Providing access to vaccines and health education for patients have become more important with the growing needs of a culturally diverse and ageing population.